2018
DOI: 10.1038/s41388-018-0330-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of lysosomal interaction of Akt with VRK2

Abstract: Serine–threonine kinase Akt (also known as PKB, protein kinase B), a core intracellular mediator of cell survival, is involved in various human cancers and has been suggested to play an important role in the regulation of autophagy in mammalian cells. Nonetheless, the physiological function of Akt in the lysosomes is currently unknown. We have reported previously that PtdIns(3)P-dependent lysosomal accumulation of the Akt–Phafin2 complex is a critical step for autophagy induction. Here, to characterize the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 106 publications
3
25
0
Order By: Relevance
“…VRK2 was first identified in 1997 as a putative serine/threonine kinase with structural similarity to vaccinia virus B1R kinase (40), and was recently characterized as a candidate gene for psychiatric and neurological disorders (41). Involvement of VRK2 in human cancer is much less studied, with few reports on its interactions with p53 (42), Bcl-xL (43), and Akt (44) and its inhibition of MAPK (45). How VRK2 expression is regulated under physiological or stressed conditions is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VRK2 was first identified in 1997 as a putative serine/threonine kinase with structural similarity to vaccinia virus B1R kinase (40), and was recently characterized as a candidate gene for psychiatric and neurological disorders (41). Involvement of VRK2 in human cancer is much less studied, with few reports on its interactions with p53 (42), Bcl-xL (43), and Akt (44) and its inhibition of MAPK (45). How VRK2 expression is regulated under physiological or stressed conditions is completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The Fbxw2 Δ/Δ mice were generated via crossing Fbxw2 fl/fl mice with EIIa-Cre transgenic mice and were viable. Mouse embryonic fibroblasts were generated from embryonic day (E)13.5 embryos of these mice as described (44) and cultured in DMEM with 15% FBS, 2 mM L-glutamine, and 0.1 mM MEM nonessential amino acids. Fbxw2 fl/fl MEFs were…”
Section: Methodsmentioning
confidence: 99%
“…Cellular regulation Metabolic effects References AKT -Growth regulation, metabolism control -Glucose metabolism: ↑ glucose transporters on cell surface → glycolysis -↓ FOXO1: ↓ gluconeogenesis -↑ PI3K/AKT/mTOR: biosynthesis of macromolecules -Insulin resistance: FOXO1 activation → ↓ AKT → hyperglycemia and phosphorylation of IRS-1, ↓ GLUT-4 translocation, ↓ glucose transported into cells -Caloric abundance: ↑ mTOR → ↑ lipid droplets Hirata et al, 2018;Józwiak, Forma, Brys, & Krzeslak, 2014;Manning & Toker, 2017;Semenkovich, Goldberg, & Goldberg, 2016;Welty, Alfaddagh, & Elajami, 2016;Zhang et al, 2018 AMPK -↑ demand for energy or caloric restriction: ↓ ATP → ↑ AMP/ATP -SIRT1 acetylation: simulates a caloric depleted state → AMPK activation → ↓ de novo lipogenesis and ↑ insulin sensitivity, lipolysis, and mitochondrial fatty acid (FA) oxidation -TSH → AMPK: ↓ HMG-CoAR and ↓ cholesterol synthesis -↓ insulin sensitivity: ↓ AMPK, defective autophagy and ROS generation -Starvation: ↑ autophagy, to ↑ nutrients available to cells → ↑ ULK1 and mTORC1 -AMPK improves NASH induced by highfat-diet: suppression of several key lipogenic factors, such as SREBP-1 (↓ triglyceride synthesis), HMG-CoAR, cholesterol synthesis; and ↑ ACC:…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Vrk2 could phosphorylate dysbindin, which will consequently enhance its ubiquitination and decrease protein stability [113]. Moreover, Hirata et al[131] found that Vrk2 interacts with Akt in the lysosomes, and the lysosomal Vrk2-Akt complex controls cellular proliferation and mitochondrial outer-membrane stabilization in the process of autophagy. Intriguingly, AKT1 is also one of the best candidate genes for SCZ [132-137].…”
Section: Functions Of Vrk2 In the Neurological Systemmentioning
confidence: 99%